Pedagogical sense of artistic disciplines from the vision of the artists (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
AbstractThe objective of this research was to identify the pedagogical significance perceived by professionals in different artistic disciplines such as visual and stage arts, as well as how the learnings from these disciplines have linked or transferred into their daily life. For the purposes of this work, the pedagogical significance was constructed from four substantial elements: epistemological, heuristic, hermeneutic and ontological. The findings indicate that in addition to the knowledge attained through the study of a discipline it acts as a valuable tool for facing life as it captivates, build passion, and unleash body awareness and feeling of freedom. Through art, the interviewed create their philosophy of life, strengthen their axiological system and reach life balance.
Keywords: Pedagogical significance; Artistic disciplines; ontological significance; Life Philosophy